What is Geographical Education? Prolegomena to the Value of Education in the School Subject Geography - Meyer, Christiane (Journal of Geography Education, 2007)
This article deals with the value of geographical education at schools from different points of view. First of all a concise, insightful review is given of the educational reform of the 1960s/70s in comparison to the current debate on national standards, since both initiated deeper reflections about the value of school subjects. Then the value of the subject Geography is presented in reference to the national standards on geographical education. After that two excursions are made: the destination of the first one is the value of elementary social studies and science at primary schools. The other excursion is a pedagogical-psychological field trip to a table of learning. These considerations lead to comments about the aim and development of geographical education for teachers-to-be at universities with regard to their first steps on the way to pedagogical content knowledge. This focus on professional development is necessary because the students will become multipliers for the value of Geography in the future of their teaching profession. In conclusion some first thoughts about a survey on the value of geographical education are presented.